Perencanaan Pembangunan Tempat P Perencanaan Pembangunan Tempat Pengelolahan Sampah Reduce, Reuse, Recycle (TPS3R) di TPA Parit Enam Pangaklpinang: Perencanaan Pembangunan Tempat Pengelolahan Sampah Reduce, Reuse, Recycle (TPS3R) di TPA Parit Enam Pangaklpinang - Shindi Widia, Shindi (SONDIR, 2025)
The research discusses the planning of the construction of a Waste Processing Facility using the Reduce, Reuse, and Recycle (TPS 3R) system at the Parit Enam Landfill in Pangkalpinang. With the increasing population growth and consumption in the Pangkalpinang area, the amount of waste generated continues to rise each year. Conventional waste management methods, such as the open dumping system, have led to excessive waste accumulation and significant environmental impacts. Therefore, the TPS 3R project is designed to address this issue through a more effective waste management system, starting from collection, sorting, to recycling. The project aims to reduce the volume of waste entering the landfill, improve the efficiency of city waste management, and create business opportunities for the community. Moreover, active participation from the government, NGOs, and the community is essential for the successful implementation of this project. The construction of the TPS 3R is expected not only to solve the problem of waste accumulation but also to support environmental sustainability and provide economic benefits to the local community.